2021
DOI: 10.33594/000000431
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Sphingosine-1-Phosphate Receptor 3 Contributes to Lung Tumor Cell Proliferation

Abstract: Background/Aims: The pleiotropic lipid mediator sphingosine-1-phosphate (S1P) exerts a multitude of effects on respiratory cell physiology and pathology through five S1P receptors (S1PR1-5). Epidemiological studies proved high levels of circulating S1P in non-small cell lung cancer (NSCLC) patients. Studies in literature suggest that high levels of S1P support carcinogenesis but the exact mechanism is still elusive. The aim of this study was to understand the mechanism/s underlying S1P-mediated lung tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
4
13
0
Order By: Relevance
“…Because S1P carries out its biological effect by interacting with its surface receptors (S1PRs) [ 1 ], we went on to evaluate their expression on H- and LK-derived PBMCs. S1PR3 was the most expressed receptor ( Figure 2 A), likewise previously observed on structural cells [ 5 ]. Whereas S1PR1 and S1PR2 were not detected on PBMCs (data not shown).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Because S1P carries out its biological effect by interacting with its surface receptors (S1PRs) [ 1 ], we went on to evaluate their expression on H- and LK-derived PBMCs. S1PR3 was the most expressed receptor ( Figure 2 A), likewise previously observed on structural cells [ 5 ]. Whereas S1PR1 and S1PR2 were not detected on PBMCs (data not shown).…”
Section: Resultssupporting
confidence: 83%
“…In another set of experiments, PBMCs were also treated with ceramidase inhibitor (D-NMAPPD, 5 µM; #SML2358; Sigma-Aldrich, Merck Life Science S.r.l., Milan, Italy), TY52156, a S1PR3 antagonist (αS1PR3, #5328; 10 µM; Tocris Bioscience, Ellisville, MO, USA), SKI II, a selective inhibitor of sphingosine kinases (SKI II, 10 µM; #2097; Tocris Bioscience, Ellisville, MO, USA), PF-543, a sphingosine-competitive inhibitor of sphingosine kinase I, SPHK I (PF543, 2 µM; #57177; Selleck Chemical, Houston, TX, USA), ABC294640 (Opaganib), a selective inhibitor of sphingosine kinase II, SPHK II (Opa, 60 µM; #915385-81-8; RedHill Biopharma, Tel-Aviv, Israel), FTI-276, a K-Ras inhibitor (FTI, 2 µg/mL; #F9553; Sigma-Aldrich, Merck Life Science S.r.l., Milan, Italy), Rapamycin, a potent and specific mTOR inhibitor (Rap, 100 ng/mL; #553210; Calbiochem, Sigma-Aldrich, Merck Life Science S.r.l., Milan, Italy), MG132, a proteasome inhibitor (MG132, 10 µM; #M8699; Sigma-Aldrich, Merck Life Science S.r.l., Milan, Italy). The concentration of all substances was chosen on the basis of the existing literature and on our previous experiments/data [ 4 , 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to S1PR2, as mentioned above, so far most studies addressing the function of S1PR3 in cancer concentrated on its role in tumor cells. There, it was shown that S1P/S1PR3 signaling is a potent driver for tumor cell migration, proliferation, angiogenesis, and metastasis in different tumor entities such as lung and breast cancer [161][162][163][164]. However, little is known about the immune cell specific function of S1PR3.…”
Section: S1pr3mentioning
confidence: 99%